Bacterial degradation of Imidacloprid and Carbosulfan under in-vitro conditions in mango (Mangifera indica) — a preliminary study (Current Horticulture, 2024)
The experiment was conducted to isolate and identify soil microflora from mango (Mangifera indica L.)orchard soil which can degrade Imidacloprid and Carbosulfan, at Central Institute for Subtropical Horticulture, Lucknow. Two bacteria, CISH I-1 and CISH C-1, were isolated from soil, both having the ability to degrade Imidacloprid and Carbosulfan. These bacteria were characterized as gram negative, rod-shaped and catalase positive bacteria, and they used these insecticides as carbon source for their growth and survival. Increase in bacterial growth was recorded up to 8 and 12 days in Imidacloprid and Carbosulfan containing media, respectively. The HPLC analysis revealed that 97 and 91 per cent of Imidacloprid and Carbosulfan were degraded in soil containing CISH I-1 and CISH C-1, respectively. Further study is required for their final identification and large-scale use in mango orchard soil.
Keywords: Imidacloprid; Carbosulfan; Bacterial degradation; Soil; Carbon source; Gram negative; Rod shaped; Insecticides